INTEGRATED APPROACH TO STRATEGIC MANAGEMENT OF HUMAN RESOURCES – RESPONSIBILITIES AT THE NATIONAL LEVEL: INTEGRATED APPROACH TO STRATEGIC MANAGEMENT OF HUMAN RESOURCES – RESPONSIBILITIES AT THE NATIONAL LEVEL - Georgiev , Georgi (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Considering the large number and variety of factors determining the efficiency and the strategic nature of human resource management in the sector, the publication presents the vision of the need for an integrated approach to the responsibilities of the two basic levels - national and institutional. Using this approach is seen as an opportunity to identify not only the most general framework, but also the new meaning and content of the processes of planning, recruitment, retention, use and discharge of people in the defence sector. This paper presents a vision on the basic responsibilities of the state towards the strategic management of human resources, as a basic process in the defence management.